Proboscidea from Kanapoi, Kenya. Issue 140 (March 2020) - Sanders, William J.
Abstract: The early Pliocene site of Kanapoi (Turkana Basin, Kenya) has a large, diverse vertebrate sample that contains the earliest representatives of the hominin genus Australopithecus . Included in this sample is an impressive assemblage of fossil proboscideans, comprised of deinotheres ( Deinotherium bozasi ), anancine gomphotheres ( Anancus ultimus ), and at least three species of elephant ( Loxodonta adaurora, a primitive morph of Loxodonta exoptata, and Elephas ekorensis ). A single specimen from high in the sequence could plausibly belong to a primitive stage of Elephas recki . A review of dental carbon isotope analyses indicates a range of dietary habits for these taxa, from dedicated browsing (deinotheres) to mixed feeding/grazing (elephants and gomphotheres), which in early Pliocene elephants corresponds to molars with greater crown height and more plates than in late Miocene confamilials, bringing their morphology more in phase with feeding behavior than was the case in their earlier relatives. Variation in feeding preferences among Kanapoi proboscideans corresponds to evidence for habitat heterogeny, including inferred substantial presence of grasses; the occurrence of multiple megaherbivores may have contributed to the fragmentation of ecosystems, positively affecting early hominin success and aiding diversification of other ungulate groups.